Pengaruh Influencer Marketing Dan Online Customer Review Terhadap Keputusan Pembelian Melalui Brand Awareness (Studi Konsumen Produk KAHF Melalui TikTok Shop Sebagai Media Pemasaran) - Ikhwan Ikhwan; Siti Asiyah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This research seeks to examine the effect of influencer marketing and online customer reviews on purchasing decisions, with brand awareness functioning as an intervening variable. The study focuses on consumers of KAHF products purchased through TikTok Shop, particularly students from the Faculty of Economics and Business at Universitas Islam Malang. A quantitative research method with an explanatory research approach was applied in this study. The respondents were selected using a purposive sampling technique, resulting in 104 participants who had experience purchasing and providing reviews for KAHF products on TikTok Shop. Data collection was carried out through questionnaires, while data analysis employed the Partial Least Squares (PLS) method. The findings reveal that influencer marketing positively and significantly influences both purchasing decisions and brand awareness. Likewise, online customer reviews demonstrate a significant positive impact on purchase decisions as well as on brand awareness. In addition, brand awareness is proven to positively affect consumer purchasing decisions. Regarding the mediating role, brand awareness is found to mediate the influence of influencer marketing on purchasing decisions and the relationship between online customer reviews and purchasing decisions, although the magnitude of the mediation effects differs.These results imply that the optimization of influencer marketing initiatives and the enhancement of online customer review quality can strengthen brand awareness, which subsequently contributes to consumer purchasing behavior. Accordingly, companies, particularly KAHF, are encouraged to reinforce their digital marketing efforts by collaborating with trustworthy influencers and promoting genuine customer feedback in order to improve their competitive position on social commerce platforms such as TikTok Shop. Keyword: Influencer Marketing, Online Customer Review, Brand Awareness, Keputusan Pembelian.